Data campaigning: between empirics and assumptions - Jessica Baldwin-Philippi (Internet Policy Review, 2019)
The use of big data in political campaigns extends far beyond micro-targeting, and has been singled out by journalists and campaign staffers alike as a powerful force that is integral to electoral victory. Current scholarship on the subject remains more mixed, however. This article provides an overview of what we know (and don't yet know) about the effects of data-campaigning across various goals of political campaigns, alongside more public facing narratives that present data campaigning as an all-powerful tactic, highlighting the gap between these two views.
Keywords: 300; Data campaigning; Political campaigns; Big data; Micro-targeting; Social media